Effectivity of Snakes and Ladders Media to Upgrade to the Summation in Children Learning Difficulties - Mutia Julaiha; Zulmiyetri Zulmiyetri (EDUTEC : Journal of Education And Technology, 2019)
This study discusses the problems found at SD N 04 Pasar Ambacang Kota Padang namely in a child who has difficulty in learning who is 13 years old who has difficulty besides skills. The purpose of this study is to reveal whether effective ladder snake media as a medium that can improve the summing ability of children with learning difficulties. The method used by researchers in this study is single-subject research (SSR) with A-B-A design. Measure and collect data on the first baseline condition (A1) continuously for 5 five observations. Intervening using snake ladder media (B) was carried out for 8 observations. Give a second baseline condition (A2) for 4 observations. Data collection techniques 0f research data is to provide tests and study documentation. Based on the results of data analysis under conditions that show an increase in the ability to add positive secera. Overlap of data at baseline (A1) intervention (B) is 40% and overlap of data at baseline (A2) and intervention is 12.5%. Based on the results of the analysis of these data shows that the snake ladder media can improve the summing ability of children with learning difficulties.